Pesticide Toxicity Profile: Copper-based Pesticides - Frederick M. Fishel (EDIS)
This document provides a general overview of use patterns and human toxicity, a listing of laboratory animal and wildlife toxicities, and a cross reference of the specific uses and common names of copper-based pesticides registered for use in Florida. This document is PI-66, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2005.